2012
DOI: 10.1021/es3023368
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Siloxanes in Environmental Matrices around a Siloxane Production Facility, and Their Distribution and Elimination in Plasma of Exposed Population

Abstract: In this study, we systematically investigated methyl siloxanes (D4−D6, L3−L16) exposure to workers from and residents living near a siloxanes manufacturing facility by measuring their concentrations in both environmental matrices (air, dust/soil, n = 62) and human plasma samples (n = 201). For the seventeen target compounds, the average concentrations in indoor matrixes from six workshops of the facility ranged from 0.6 μg/m 3 to 2.7 mg/m 3 in air samples and from 0.36 μg/g to 1.16 mg/g in dust samples, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 32 publications
2
22
0
2
Order By: Relevance
“…General population In 519 plasma samples from general population, no linear siloxane was detected, while three cyclic siloxanes (D4-D6) were detected, with concentrations ranging from 1.10-5.95 ng/mL (df = 3.7%), 1.98-6.22 ng/mL (df = 3.7%), and 1.85-7.50 ng/mL (df = 1.7%) for D4, D5, and D6, respectively (Table 1). This result was consistent with previous studies from China and Germany (Xu et al, 2012;Flassbeck et al, 2001), which reported that methyl siloxanes were hardly found in plasma of general population. Although Hanssen et al (2013) reported higher detection frequencies of cyclic siloxanes -85%, 18%, and 5% for D4, D5, and D6, respectively -in plasma of general population (postmenopausal women) from Norway, their concentrations were also at low levels -2.93-12.7 ng/mL, 1.44-3.94 ng/mL, and 2.67-3.17 ng/mL for D4, D5, and D6, respectively.…”
Section: Concentrations Of Methyl Siloxanes In Human Plasmasupporting
confidence: 94%
See 3 more Smart Citations
“…General population In 519 plasma samples from general population, no linear siloxane was detected, while three cyclic siloxanes (D4-D6) were detected, with concentrations ranging from 1.10-5.95 ng/mL (df = 3.7%), 1.98-6.22 ng/mL (df = 3.7%), and 1.85-7.50 ng/mL (df = 1.7%) for D4, D5, and D6, respectively (Table 1). This result was consistent with previous studies from China and Germany (Xu et al, 2012;Flassbeck et al, 2001), which reported that methyl siloxanes were hardly found in plasma of general population. Although Hanssen et al (2013) reported higher detection frequencies of cyclic siloxanes -85%, 18%, and 5% for D4, D5, and D6, respectively -in plasma of general population (postmenopausal women) from Norway, their concentrations were also at low levels -2.93-12.7 ng/mL, 1.44-3.94 ng/mL, and 2.67-3.17 ng/mL for D4, D5, and D6, respectively.…”
Section: Concentrations Of Methyl Siloxanes In Human Plasmasupporting
confidence: 94%
“…Meanwhile, 519 participants from seven cities in northern China, without industrial work experiences, served as the control group. It should be noted that although some control participants in the present study were from the same city with the participants in our previous study (Xu et al, 2012), the participants had no overlap between these two studies. During January to March 2012, each of 487 occupational participants and 270 control participants provided one plasma sample (5 mL) voluntarily.…”
Section: Plasma and Abdominal Fat Samplesmentioning
confidence: 75%
See 2 more Smart Citations
“…Dentro de esta familia de compuestos los metilsiloxanos de cadena corta conocidos como metilsiloxanos volátiles (VMS), han recibido una especial atención en los últimos años debido a su elevada capacidad de bioacumulación, [1][2][3][4][5][6][7] potencial cancerogenicidad [8][9][10] y amplia distribución ambiental. [11][12][13][14][15][16][17][18][19][20][21] Estos compuestos se presentan en conformaciones lineales o cíclicas tal y como se ilustra en la Figura 1, y se caracterizan principalmente por presentar una elevada presión de vapor (2.3 -5620 Pa a 25 o C) y baja solubilidad en agua (0.07 -1560 µg L -1 a 25 o C). [22][23][24] Entre sus principales aplicaciones se encuentra su uso como constituyentes básicos en cosméticos y productos de higiene personal, como materiales de partida para la síntesis de polisiloxanos de elevado peso molecular, y su empleo como aditivos en productos de limpieza, desengrasantes, lubricantes, disolventes, pinturas, lacas y barnices.…”
Section: Introductionunclassified